The Relations Between the European Union and the Russian Federation Prior and After the Creation of the Common Economic Space - Razvan-Alexandru Gentimir (CES Working Papers, 2015)
Due to its geographical position and its cultural links, Russia has always had a special relation with Europe. In its attempt to shape its own place on the global stage, the Russian Federation has sometimes seen itself as an authentic European state, while in other cases and circumstances, it strongly supported and claimed its “Eurasian” features. Due to the enlargement of the European Union and its rise as a heavy international player, the European Union has turned into a geographical neighbor of the Russian Federation. From this perspective, it is not a surprising fact that the Russian Federation is to develop specific relations and shape a foreign policy with strategic features regarding the European Union. The institutional cooperation between the European Union and the Russian Federation aims at shaping a series of common objectives regarding the relations between the two sides and defining the actions needed in order to reach the proposed objectives, the implementation of the common projects considering the agreed order of priorities.
Keywords: F00; F15; F36; F42; F50; 330; Russian Federation; European Union; international stage; international player; cooperation; objectives